Asset prices in monetary policy rules: should they stay or should they go? - Pacheco, Luís Miguel (2013)
The nature of the relationship between asset price movements and monetary policy is a currently hotly debated topic in macroeconomics. We analyse that relationship using a standard dynamic stochastic general equilibrium model, augmented by an equation featuring the asset prices deviations from a trend value. The calibration and subsequent simulation of that model allows us to conclude that it wouldn’t be desirable to include asset prices in the monetary policy rule, because of the higher interest rate and inflation volatility. The inclusion of a reaction to asset prices deviations in the monetary policy rule would only be justifiable in the context of a strong output gap sensibility to them and, even in that case, the gains of welfare would be so small that shouldn’t offset the costs attached to an explicit tracking of asset prices behaviour by the monetary authority. In conclusion, our results are consistent with a benign neglect view by the monetary authority towards asset prices. This attitude, where the ECB clearly fits in, implies that central banks could act in response to asset prices movements when there’s the need to avoid a sharp correction in the markets, which could have destabilising effects over the economy.